Federal Credit Agencies and the Structure of Money Markets, Interest Rates and the Availability of Capital - Freedman, Robert (Quarterly Journal of Economics, 1955)
I. Introduction, 421. — II. The influence of federal agencies on the "costs" of lending, 421. — III. Agency influences on the availability of capital and rate patterns, 428. — IV. Conclusions, 443.